STUDI LITERATUR: UPAYA MENINGKATKAN MOTIVASI LITERASI MELALUI PROGRAM LITERASI HARIAN DI SEKOLAH DASAR - Risfi Aulya Hanni; Haryadi; Bernadus Wahyudi Joko Santoso (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to further explore effective efforts to enhance students’ literacy motivation, particularly in Indonesian language learning at the elementary school level. This research employed a systematic literature review method, analyzing national accredited (Sinta-indexed) and international scholarly publications published between 2021 and 2025. The analysis involved identifying, evaluating, and interpreting relevant studies to construct a comprehensive synthesis of current literacy practices. The findings reveal five major strategic approaches: (1) strengthening daily literacy programs through reflective and follow-up activities; (2) implementing project-based and collaborative literacy learning; (3) integrating local cultural content to build emotional relevance and character values; (4) utilizing interactive digital media such as digital storytelling and pop-up books; and (5) fostering collaboration among schools, families, and literacy communities. Within the framework of the Merdeka Curriculum, these strategies align with the development of the Pancasila Student Profile, emphasizing independence, creativity, and critical reasoning.